Similar successional development of functional community structure in glacier forelands despite contrasting bedrocks. (4th April 2021) - Greinwald, Konrad; Gebauer, Tobias; Musso, Alessandra; Scherer‐Lorenzen, Michael
Abstract: Questions: Primary plant succession is expected to be driven by habitat filtering and competitive exclusion. However, such findings typically come from experimental or single‐site case studies. As a result, we lack field studies that investigate the functional community structures across successional series with differing site conditions. Here, we address the following question: how do plant trait patterns and functional diversity change along two chronosequences with distinct bedrocks? Methods: We established two soil chronosequences with contrasting bedrock types (siliceous vs calcareous) in the Swiss Alps spanning a terrain age gradient of 13, 500 years. We analysed plant ecological strategies at 40 plots per glacier foreland relating six functional traits to terrain age using RLQ analysis. We used the variation in plant ecological strategies revealed by RLQ analysis to calculate indices of functional diversity and analysed their temporal development with terrain age. Results: The RLQ analysis revealed that canopy height and dispersal type were significantly associated with terrain age. In both glacier forelands, functional richness (FRic) increased with terrain age, suggesting similar development of niche differentiation along the chronosequences, irrespective of bedrock types. In addition, we observed a decrease of functional evenness (FEve) and functional divergence (FDiv) in both sites, indicating an overall trend to habitat filtering. Conclusions: The results support the idea of a similar development of functional community structure along the two chronosequences, underlining the deterministic model of functional structure during succession. The functional approach of this study improves knowledge of the adaptive strategies of plant communities colonising glacier forefields and highlights the potential of comparing successional series with differing site conditions to gain a deeper understanding of successional drivers and underlying mechanisms. Abstract : We present a comparative study investigating the temporal development of functional community structure in two proglacial chronosequences with contrasting bedrocks. We found evidence for habitat filtering in both chronosequences. Furthermore, plant functional traits and functional diversity indices showed similar patterns along the successional gradients suggesting a deterministic model of functional community structure development in glacier forelands.